Experimental investigation on interlaminar tension strength of curved composite laminates subjected to four-point bending load. (2nd January 2023) - Huang, Wenchao; Li, Changyou; Xie, Liyang; Jia, Dawei; Zhang, Xiulu; Fang, Caiwen
Abstract : The present work aims at experimentally quantifying the effect of the process, environmental, and geometric conditions on the interlaminar tension stress (ILTS) performance of curved composite laminates. First, an innovative experimental matrix is established considering the material and process variability, environmental conditions, lay-up, thickness, radius-to-thickness ratio, defects, and thermal cycles. Subsequently, four-point bending tests are performed on the L-shaped laminated specimens. The effects of each condition on ILTS are obtained, with an interpretation of the corresponding mechanism. The results demonstrated that the material and process variability for the ILTS is about 24%. The stress of the hygrothermally aged specimens was reduced by 34.84%, but the performance was improved by 64.63% at −55 °C. Moreover, it is worth noting that, among all the design factors, the initial defects resulted in a significant stress reduction of up to 63.94%. Finally, the design allowable values under different environmental conditions were accurately calculated by the proposed method. The experimental results have been compared with corresponding observations reported in the literature, exhibiting a good agreement. Consequently, the conclusions of this study are highly useful for civil aircraft design applications.